INCREASE THE LITTER SIZE OF BALI SOWS USING P.G. 600 INJECTION AND FLUSHING IN THE FORM OF GLUCOSE - Suyadnya, P. (Majalah Ilmiah Peternakan, 2007)
SUMMARY The aim of this study was to increase the litter size of Bali sows using P.G. 600 injection and flushing in the form of glucose. A total of 32 Bali sows and one mature Bali boar were used. All of the Bali sows have farrowed twice. This study used Completely Randomized Design (CRD) with 2 x 2 Factorial arrangement. P.G. 600 as the first factor (H) was divided into two, i.e. without injecting P.G. 600 (H0) and with injecting P.G. 600 (H1). Flushing as the second factor (F) was also divided into two, i.e. without flushing (F0) and with flushing (F1). Thus, there were four treatment combinations in this study, namely, H0F0 (Control), H0F1 , H1F0 , and H1F1 , with eight replications. A total of 10 ml P.G. 600 or 800 i.u. FSH and 400 i.u. LH was administered to each sow by subcutaneous injection behind the ear immediately after weaning its piglets. Flushing to each sow was started at weaning its piglets until the time of mating by adding 400 g of glucose a day to the basal ration. The result of this study showed the average litter size of Bali sows receiving combined treatments H0F0 (Control), H0F1 , H1F0 , and H1F1 were 6.63 + 1.51, 7.63 + 1.30, 7.50 + 1.07 and 9.50 + 1.41 piglets. The total litter weights at birth per-sow were 3.063 + 0.658, 4.547 + 0.707, 3.453 + 0.596, and 5.191 + 1.293 kg; and the average birth weights per-individual were 0.472 + 0.093, 0.604 + 0.101, 0.466 + 0.094, and 0.560 + 0.093 kg, respectively. Statistical analysis showed, the effect of injecting P.G. 600 (H1F0) increased significantly (P < 0.05) the litter size of Bali sows, however, the litter weight at birth per-sow and birth weigth per-individual were not affected. Both effects of flushing (H0F1) and treatment combination of P.G. 600 injection and flushing (H1F1) increased significantly (P < 0.05) the litter size, litter weight at birth per-sow and birth weight per-individual of Bali sows. There were no interaction effects observed between treatments to the all of variables recorded on this study.